Factors Influencing the Dimensions of Service Quality at Bank Central Asia Syariah Banda Aceh Branch - Hajriyanti, Rahmi; Al Bahri, Fauzan Putraga; Zahra, Rita (Indonesian Journal Economic Review (IJER), 2024)
In order to improve the quality of service to customers, Bank Central Asia Syariah Banda Aceh Branch tries to identify the needs and desires of customers by creating good and superior service quality and trying to provide satisfactory service to customers, seen from cultural factors between customers and the magnitude of service quality, so that all problems and obstacles are handled well and detected quickly and the risks that may be faced will be reduced. Therefore, several problems were identified whether cultural factors affect the dimensions of service quality at Bank Central Asia Syariah Banda Aceh Branch and which cultural dimension factors are dominant in influencing the dimensions of service quality at Bank Central Asia Syariah Banda Aceh Branch To obtain data and information, the author conducted a study by taking a location at. Bank Central Asia Syariah Banda Aceh Branch Jl. T. Nyak Arief while the object of this study is research on factors that affect the dimensions of service quality in this case is the cultural dimension factor carried out in the city of Banda Aceh. The population in this study were all customers of Bank Central Asia Syariah Banda Aceh Branch. While the sample in this study was determined by the sampling method. The sampling method used is Quota Sampling with a total of 50 respondents. Based on the results of the discussion, it is obtained a hypothesis that accepts the alternative hypothesis as part of the factors that influence the dimensions of service quality of Bank Central Asia Syariah Banda Aceh Branch, because the results of simultaneous testing obtained F count of 10,426 while F table at the significance level α = 5% is 2,427. This shows that F count> F table, with a significance of 0.000. This proves that the variables of Power Distance, Individualism, Masculinity, Uncertainty Avoidance and Long-Term Orientation together have a significant effect on the service quality dimensions of Bank Central Asia Syariah Banda Aceh Branch. From the results of the t-test (partially) it shows that only three variables are significant, namely the Power Distance variable, the Individualism variable and the Long-Term Orientation variable and each independent variable has a significant effect on the dependent variable (Factors that influence the service quality dimensions of Bank Central Asia Syariah Banda Aceh Branch because it has a t-count value that is greater than the t-table value and the other two variables, namely the Masculinity variable and the Uncertainty Avoidance variable, have a low significance value to influence the service quality dimensions of Bank Central Asia Syariah Banda Aceh Branch.